Leptospirosis in Brazil: an approach to public health (Research, Society and Development, 2022)
Objective: To present the distribution and epidemiological analysis of confirmed leptospirosis cases in the country from 2010 to 2019. Methodology: This is an epidemiological, retrospective and descriptive study of a population nature, using secondary data, obtained from the Information System of Notifiable Diseases (SINAN). Evaluating aspects related to gender, age group, ethnicity, education, confirmation criteria, clinical evolution, regions of residence, federation units, source and characteristics of the infection site and, finally, patients of gestational age in the country, using the TABNET and Microsoft Office Excel 2019 programs. Results: The epidemiological profile of the disease in Brazil was prevalent in males (79.5%), with a greater number of cases in the 20-39 age group (39.5%) and with schooling in the 5th to 8th grades of elementary school (15.8%). There was also a greater confirmation of white patients (45.0%). It was also possible to verify that more than half of the cases were in the urban area (54.40%) and in households (41.0%). Highlight for the Southeast (32.60%), South (32.40%), with and in the state of São Paulo (22.5%). As for the clinical outcome, there was a high percentage of cured individuals (83.1%) and 8.60% lethality, in which 0.85% of the cases died due to the disease. Most pregnant women in the 2nd trimester of pregnancy (32.3%) of the notified cases; followed by the 3rd quarter with 27%. Conclusion: Thus, it is concluded that the application of personal preventive attitudes and the duty of the public administration to provide basic sanitation, health education and infrastructure.